The education of the librariens of high qualification in universities - Gudauskas, Renaldas (Knygotyra, 1987)
Attempts to organize higher library education in Lithuania were made long ago. An epizodic course in bibliography was read in the old Vilnius University in 1829–1830.After the restoration of Soviet power in Lituania in 1940 the Chair of bibliology was established at Vilnius State University, the course of bibliography was read. Lectures to start the preparation of skilled librarians and bibliographers were planed to read begining from the autumn of 1941. The work was interrupted by the war and nazi occupation.The department of Librarianship was founded at Vilnius State University in 1949 (the Librarianship Chair in 1952; the Scientific Information Chair in 1973). During a short period the Chairs achieved good results in various branches. They developed the scientific and research activity in librarianship and bibliography and gave skilled specialists for the libraries of our republic.During the last years more than 2000 specialists were trained in the University. They were appointed to work in different public, children, school, scientific, special and technical libraries, in scientific information offices.The great experience of library staff training gathering in for 40 years in the USSR’ universities shows that librarian’s profession does not contradict to the conception of university education. This article reveals specification of library staff training in university conditions, shows achievements and possibility of university library education, grounds necessity to carry out scientific researches in modern problem of development and perfection professional training of library staff in the USSR universities.Correspond to the aims and possibilities of university education the author proposes scientifically elaborate experimental individual curiculum, connected with contemporary needs of librarianship theory and practice, as a main way to perfect teaching. The search of more optimum way for organization and perfection library staff training – one of the main problems of soviet librarianship; it is necessary to mobilize all potential possibilities for its allowance.